Pengaruh Kompetensi Kepribadian Guru Pendidikan Agama Kristen Terhadap Karakter Peserta Didik Pada Tingkatan Sekolah Menengah Pertama - Zefanya Andriani Fitura Sirait; Dorlan Naibaho (JURNAL ILMIAH RESEARCH STUDENT, 2023)
Student character is a guarantee for the future, the character formed during this period will bear fruit in the future, in other words, student character can be said to be a guarantee for the future. The character of students is very dependent on the teacher who teaches them, although in reality it is not only the world of education that influences character, such as the community environment and family environment. However, at this time, schools play a very important role in forming the character of students, more specifically, Christian Religious Education Teachers are very responsible for forming the character of students. Not only intelligent, polite, polite and so on, but Christian Education Teachers also direct students to have character based on faith, belief in God. This is what makes students act and behave in accordance with God's laws. This is one of the roles and responsibilities of Christian Religious Education Teachers. Equipped with personality competencies, Christian Religious Education Teachers will become the center of attention of students and even other teaching teachers. Therefore, Christian Religious Education Teachers must have good, steady, consistent, mature and authoritative personality competencies. This is what the participants will be taught and imitated and will be used as a benchmark for their own character.